1961
DOI: 10.1136/bmj.1.5231.1006
|View full text |Cite
|
Sign up to set email alerts
|

Use of Corticosteroids in Infertility Associated with Hirsuties and Oligomenorrhoea

Abstract: ADRENAL PSEUDOHERMAPHRODITISMBMJouT=AL_ hirsutism seemed to argue against the latter, though from other points of view this seemed to be the most probable diagnosis. The findings on investigation soon settled the point: the very high 17-KS and 17-KGS and the elevated P'triol and P'diol pointed convincingly to adrenal hyperfunction, while the prompt response to prednisone suppression ruled against an adrenal tumour. The sex chromatin indicated female genetic sex, and laparotomy confirmed the existence of normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1966
1966
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…There have been reports of the value of adrenal suppression (1). The effect on hair growth is usually disappointing (2) although menstrual regularity may be restored and infertility corrected (3). There are a few reports on the results of ovarian suppression in the treatment of hirsutism (4)(5)(6) and it has been suggested that the hair growth may be appreciably reduced in some patients.…”
mentioning
confidence: 98%
“…There have been reports of the value of adrenal suppression (1). The effect on hair growth is usually disappointing (2) although menstrual regularity may be restored and infertility corrected (3). There are a few reports on the results of ovarian suppression in the treatment of hirsutism (4)(5)(6) and it has been suggested that the hair growth may be appreciably reduced in some patients.…”
mentioning
confidence: 98%